Expansion and Contraction of Variable Rank Coals during the Exchange Sorption of CO and CH - Grażyna Ceglarska-Stefańska; Katarzyna Zarębska (Adsorption Science & Technology)
The influence of the physical and chemical properties and the composition of the sorbed gas on the sorption capacity of hard coal must be taken into account in an analysis of such coals as specific collectors of mine gases. The analysis presented was based on a comparison of the results of sorption and expansion studies of single gases (CO 2 and CH 4 ) and their mixtures on two hard coals (V daf : 40.87% and 22.32%). The work presented was undertaken in an attempt to determine the influence of the sorptive deformation of the coals, caused by the pre-sorption of CO 2 , on the variation of their external dimensions during CH 4 sorption and vice versa, and during sorption of a mixture of these gases. In addition, it was anticipated that the work could answer the question as to which of these gases would enrich the desorbed gas. Knowledge of these effects should facilitate further exploration of the relationship between the properties of a hard coal and methane evolution to establish those factors that enhance the rate and effectiveness of the process.